Power Generation Pricing Model Based on Long Rung Marginal Cost Methodology - Priyanka Roy; Abhijit Chakrabarti (Institute of Advanced Engineering and Science, 2012)
This paper proposes a long run marginal cost based formulation for reflecting the usage based pricing of electrical power. The aim of this paper is to develop a novel method that can price the real power on a long term basis in a multi-machine power system. The proposed method has shown that the cost of future investment is governed by the perturbation of generating power. The economic efficiency of the proposed model is demonstrated in a 203 buses 267 lines 23 machines real power system of eastern part of India where total 23 generators are categorized in 5 types according to their ratings and analyzed the price at their optimal operating condition with 10% loading variation.DOI:http://dx.doi.org/10.11591/ijece.v2i2.191